2017
DOI: 10.3389/fpubh.2017.00341
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Preferences for Daily, Event-Driven, or Periodic HIV Pre-Exposure Prophylaxis among Gay and Bisexual Men in the PRELUDE Demonstration Project

Abstract: IntroductionThe effectiveness of daily pre-exposure prophylaxis (PrEP) is well established. However, there has been increasing interest in non-daily dosing schedules among gay and bisexual men (GBM). This paper explores preferences for PrEP dosing schedules among GBM at baseline in the PRELUDE demonstration project.Materials and methodsIndividuals at high-risk of HIV were enrolled in a free PrEP demonstration project in New South Wales, Australia, between November 2014 and April 2016. At baseline, they complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 37 publications
(31 reference statements)
1
29
1
1
Order By: Relevance
“…Regarding the type of PrEP use, previous studies in Belgium, the Netherlands and Australia found that between 23.5% and 48% of the participants preferred non-daily PrEP [12,[28][29][30][31]. A single-centre study in France found the preference for on-demand PrEP to be as high as 75.6% [9].…”
Section: Discussionmentioning
confidence: 98%
“…Regarding the type of PrEP use, previous studies in Belgium, the Netherlands and Australia found that between 23.5% and 48% of the participants preferred non-daily PrEP [12,[28][29][30][31]. A single-centre study in France found the preference for on-demand PrEP to be as high as 75.6% [9].…”
Section: Discussionmentioning
confidence: 98%
“…Considerable uptake of this biomedical intervention has been observed in mostly men who have sex with men (MSM). Recent studies conducted in this population have shown that there is substantial variation in whether MSM prefer to initiate daily over event-driven PrEP [ [3] , [4] , [5] 6 ]. An individual's choice of regimen over time is also likely to fluctuate with changing sexual and social contexts [7] .…”
Section: Introductionmentioning
confidence: 99%
“…While there are data on the motives to use daily PrEP , little is known about the reasons to choose between daily and event‐driven PrEP, to switch between these regimens, or to discontinue PrEP use altogether in a setting that offers both regimens. The majority of previous studies reported on situations in which event‐driven PrEP was only a hypothetical option , and where stops were associated with daily adherence problems and reduced risk . Data on actual choices between daily and event‐driven PrEP among MSM are only available from three studies in the European setting, the roll‐out programme in France , the Be‐Prepared study in Belgium , and our own study, the Amsterdam PrEP (AMPrEP) demonstration project in the Netherlands .…”
Section: Introductionmentioning
confidence: 99%